2015
DOI: 10.1016/j.jelekin.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Force irradiation effects during upper limb diagonal exercises on contralateral muscle activation

Abstract: The aim of this study was to explore the force irradiation effects of upper limb isometric diagonal exercises on shoulder muscle activities. Interactions among diagonal directions, contraction intensities (moderate and maximum) and sex were assessed. Thirty healthy subjects (11 males) performed isometric unilateral diagonal exercises based on proprioceptive neuromuscular facilitation technique in an isokinetic dynamometer with their dominant upper limbs. The second diagonal for flexion and for extension were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
1
10
1
1
Order By: Relevance
“…In addition, another study showed that force irradiation during upper limb diagonal exercises is affected by diagonal direction, contraction intensity, and gender when performed by healthy participants [5]. Our results in a previous article [6] match with some of these ndings.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, another study showed that force irradiation during upper limb diagonal exercises is affected by diagonal direction, contraction intensity, and gender when performed by healthy participants [5]. Our results in a previous article [6] match with some of these ndings.…”
Section: Introductionsupporting
confidence: 88%
“…The data normality was tested and con rmed by the Kolmogorov-Smirnov test. We used a repeated-measures ANOVA test for each muscle in different tasks that were applied [muscle x (5…”
Section: Discussionmentioning
confidence: 99%
“…When it is difficult to train the injured areas directly in sport rehabilitation, the cross training that improves strength of injured part using the opposite part is a form of irradiation (Abreu et al, 2015; Kofotolis and Kellis, 2007; Reznik et al, 2015). The mechanism is uncertain and may be caused by the bilateral distribution of the descending motor pathways, neural overflow and muscular system (Kofotolis and Kellis, 2007; Røe et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation is governed by the principle of training specificity (isometric or dynamic), and eccentric contractions cause greater strength gains when compared to concentric contractions [7,8]. This strength gain can be propagated to the ipsilateral agonist muscle, to contralateral limb [9] or having origin in trunk and irradiate for the lower and / or upper limbs [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors used electromyography (EMG) to evaluate the irradiation produced by PNF because is possible to record the activity of motor units that are recruited during muscle contractions [7,14,9]. The effects of PNF in the brain is evaluated using the Functional magnetic resonance imaging (fMRI), a tool also a lot highlighted in the studies of PNF [14].…”
Section: Introductionmentioning
confidence: 99%